2012
DOI: 10.1007/978-3-642-28509-7_32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implicit and Explicit Affective Labeling on a Recommender System’s Performance

Abstract: Abstract. Affective labeling of multimedia content can be useful in recommender systems. In this paper we compare the effect of implicit and explicit affective labeling in an image recommender system. The implicit affective labeling method is based on an emotion detection technique that takes as input the video sequences of the users' facial expressions. It extracts Gabor low level features from the video frames and employs a kNN machine learning technique to generate affective labels in the valence-arousal-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Each of the two approaches has its pros and cons. Again, Tkalcic et al [19] showed that content-based recommendation still works better when explicit labels are used, probably due to the still low accuracy of algorithms that detect affective responses. For this reason, research on improving affective implicit tagging is very active and opening up to a wide range of investigations.…”
Section: E E E P R O O Fmentioning
confidence: 99%
“…Each of the two approaches has its pros and cons. Again, Tkalcic et al [19] showed that content-based recommendation still works better when explicit labels are used, probably due to the still low accuracy of algorithms that detect affective responses. For this reason, research on improving affective implicit tagging is very active and opening up to a wide range of investigations.…”
Section: E E E P R O O Fmentioning
confidence: 99%
“…Throughout the last two decades, personalization became the core feature for the effectiveness of RS in a wide range of > REPLACE THIS LINE WITH YOUR MANUSCRIPT ID NUMBER (DOUBLE-CLICK HERE TO EDIT) < domains [7,32,40,41], with several trying to predict the users' preferences based on their personality [42][43][44][45][46][47][48][49]. Nunes, Cerri and Blanc [33] proposed the use of personality traits to recommend a president candidate for voters in the elections in France.…”
Section: B Personality-based Recommender Systemsmentioning
confidence: 99%
“…Thus far we have focused on the implications of predictive algorithms based on one's own previous behavior. However, algorithms also serve content based on the prior behavior of similar others or people in general (Aggarwal, 2016;DiResta, 2020;Ricci et al, 2011;Tkalcic et al, 2009). For example, an in-depth analysis of Google search results suggests that they are both tailored to one's own prior search history as well as the search history of other users with a similar profile (Feuz et al, 2011).…”
Section: -314)mentioning
confidence: 99%